Prevalence of reagent test-kit use and perceptions of purity among ecstasy users in an electronic dance music scene in New York City - Palamar, J.; Barratt, Monica (Wiley-Blackwell Publishing Ltd., 2019)
© 2018 Australasian Professional Society on Alcohol and other Drugs Introduction and Aims: Ecstasy users in the electronic dance music scene are at high risk for using ecstasy adulterated with new psychoactive substances and/or methamphetamine. We examined self-reported testing of ecstasy among users in this scene. Design and Methods: We surveyed individuals (aged 18–40 years) entering electronic dance music parties in New York City in 2017. Past-year ecstasy users (n = 351) were asked if they had tested their ecstasy in the past year. We estimated prevalence and correlates of having tested one's ecstasy. Results: 23.1% reported having tested their ecstasy in the past year. Those with some college (adjusted prevalence ratio [aPR] = 0.49, P = 0.014) or a college degree (aPR = 0.41, P = 0.025) were less likely to test their ecstasy than those with a high school diploma or less. Using ecstasy pills (aPR = 1.89, P = 0.036) or crystals (aPR = 1.90, P = 0.006) =3 times in the past year was associated with increased likelihood of testing one's ecstasy, and purchasing from an unknown or untrustworthy dealer was associated with decreased likelihood (aPR = 0.63, P = 0.034) of testing one's ecstasy. Half (51.1%) of ecstasy users reported finding out or suspecting their ecstasy had contained a drug other than MDMA. Of these, 49.2% reported finding out their ecstasy contained methamphetamine or speed/amphetamine. Most ecstasy users reported that they would be less likely to use again upon learning their ecstasy contained ‘bath salts’ (54.8%) or methamphetamine (54.3%). Discussion and Conclusions: Drug testing appears to help ecstasy users detect adulterants and results can help inform harm reduction efforts. Less frequent users in particular may require education about adulteration and drug-testing.